RDNA analysis of the Red Sea seagrass, Halophila, reveals vicariant evolutionary diversification. Issue 7 (3rd October 2018) - Nguyen, Xuan-Vy; Kletschkus, Elia; Rupp-Schröder, Sofia Isabell; El Shaffai, Amgad; Papenbrock, Jutta
Abstract : The effects of opening the Suez Canal as a connection between the Red Sea and the Mediterranean Sea were reported for a number of marine species. However, the evolutionary origin of the seagrasses in the Red Sea and the linking population genetics of seagrasses between the Arabian Sea, the Gulf of Aden, the Red Sea and the Mediterranean Sea have not yet been investigated in detail. The invasion of Halophila stipulacea Asch. from the Red Sea into the Mediterranean Sea after the opening of the Suez Canal was already recorded. We hypothesize that Halophila ovalis populations in the Red Sea developed through long-term historical processes such as vicariant evolutionary diversification. Seagrass samples were collected along the Egyptian coastline of the Red Sea and analysed by the molecular marker ITS. The sequences were compared with published ITS sequences from seagrasses collected in the whole area of interest. In this study, we reveal the linking population genetics, phylogeography and phylogenetics of two dominant seagrass species, Halophila stipulacea and Halophila ovalis, among species collected in the Red Sea and worldwide. The results indicate that the Red Sea Halophila ovalis populations do not group to Halophila ovalis worldwide, and Halophila major, Halophila ovalis collected worldwide and Halophila ovalis collected at the Red Sea are sister clades. Hence, vicariant evolutionary diversification for Halophila ovalis may occur in the Red Sea.